2009
DOI: 10.1063/1.3116509
|View full text |Cite
|
Sign up to set email alerts
|

Thermal diffusivity of aromatic polyimide thin films by temperature wave analysis

Abstract: Thermal diffusivity of alkali and silver halide crystals as a function of temperature J. Appl. Phys. 109, 033516 (2011); 10.1063/1.3544444 Thermal conductivity/diffusivity of Nd 3 + doped Gd V O 4 , Y V O 4 , Lu V O 4 , and Y 3 Al 5 O 12 by temperature wave analysisThe heat transport properties of aromatic polyimide thin films have become more important in the use for the electric insulation in the microelectronic devices with highly integrated circuits. The various kinds of measuring methods have been applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 108 publications
1
73
0
1
Order By: Relevance
“…The TC  of sBPOD, on the other hand, is relatively high because a larger proportion of PI chains contributes to heat propagation in the out-of-plane direction. It is confirmed by the fact that reported in-plane TD (TD // ) of sBPPD and sBPOD are approximately 5-fold and 2-fold of their TD  , respectively [9].…”
Section: Thermal Conductivity Of Aln/pi Filmssupporting
confidence: 61%
See 1 more Smart Citation
“…The TC  of sBPOD, on the other hand, is relatively high because a larger proportion of PI chains contributes to heat propagation in the out-of-plane direction. It is confirmed by the fact that reported in-plane TD (TD // ) of sBPPD and sBPOD are approximately 5-fold and 2-fold of their TD  , respectively [9].…”
Section: Thermal Conductivity Of Aln/pi Filmssupporting
confidence: 61%
“…It has been reported that the major factors contributing to TC of PIs are (1) the chemical structure of the repeating unit, (2) the orientation of chains, and (3) the degree of molecular packing [8][9][10]. In dielectric materials, heat is transferred via quantized lattice vibrations called 'phonons'.…”
Section: Thermal Conductivity Of Aln/pi Filmsmentioning
confidence: 99%
“…Out-of-plane thermal diffusivity (D  ) of pristine and composite films was measured using a temperature wave analyzer (ai-phase mobile 1u) at room temperature [6,7]. The applied voltage was 1.8 V, and the film thicknesses were 25−100 μm.…”
Section: Measurementsmentioning
confidence: 99%
“…The thermal expansion behaviors of PI film BPADA-SDA, and copolymers) were evaluated by Shimadzu TMA-60 (Shimadzu, K a fixed load of 1.5 g and a heating rate of 10 °C/min. Differential scanning c Shimadzu DSC-60, Shimadzu, Kyoto, Japan) was used to monitor the cross-linkin The temperature was raised from room temperature to 300 °C at a heating rate thermal diffusivities along the out-of-plane direction (D ⏊ ) of PI and BMI/PI com measured at room temperature using an AC temperature wave analyzer (ai-Ph phase Co. Ltd., Tokyo, Japan) [11,12]. Each film was measured ten times at differ value of pristine BPADA-MPD film is lower than that of pristine TF film because of the flexible ether and bent m-phenylene linkages in its main chain, which coincides well with the analysis proposed in our previous study [22].…”
Section: Measurementsmentioning
confidence: 99%
“…The mal diffusivities along the out-of-plane direction (D ⏊ ) of PI and BMI/PI composite films were sured at room temperature using an AC temperature wave analyzer (ai-Phase mobile 1u, aise Co. Ltd., Tokyo, Japan) [11,12]. Each film was measured ten times at different locations, and ) of PI and BMI/PI composite films were measured at room temperature using an AC temperature wave analyzer (ai-Phase mobile 1u, ai-phase Co. Ltd., Tokyo, Japan) [11,12]. Each film was measured ten times at different locations, and the average value was adopted as the experimental value.…”
Section: Measurementsmentioning
confidence: 99%